2020
DOI: 10.1002/pat.4916
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a high thermal conductivity for segregated BN/PLA composites via hydrogen bonding regulation through cellulose network

Abstract: Normally, the effective dispersion of thermal conductive fillers is a prerequisite for ensuring thermally conductive networks formed in polymer composites. In this work, a facile method was provided by using cellulose to alter the distribution state of boron nitride (BN) for the preparation of high thermally conductive polylactic acid (PLA). After powder mixing and hot‐pressing process, the Cellulose@BN was located at the boundaries of PLA granules to form consecutive thermally conductive networks with more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Notably, redshift and broadening of the OH-stretching fundamental band in infrared spectra were found by comparing PLA and ABCTPs (Figure 2d), which confirmed the formation of hydrogen bonds (between -Br of PS chains and -OH of PLA chains). [11] Free-standing HEMI-ASPE membranes, which consist of NB(PS(-b-PLA)-b-MeOPEG miktoarm star terpolymers, PEO, and lithium salt (sodium salt) for AS-LMBs (AS-SMBs) (HEMI-ASPE-Li and HEMI-ASPE-Na, respectively), were prepared by the solution casting technique. To visually reveal the superiority of the HEMI-ASPEs, reference samples of the pure PEO-based ASPEs for AS-LMBs and AS-SMBs (PEO-ASPE-Li and PEO-ASPE-Na) were also prepared with the same salt/polymer mass ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, redshift and broadening of the OH-stretching fundamental band in infrared spectra were found by comparing PLA and ABCTPs (Figure 2d), which confirmed the formation of hydrogen bonds (between -Br of PS chains and -OH of PLA chains). [11] Free-standing HEMI-ASPE membranes, which consist of NB(PS(-b-PLA)-b-MeOPEG miktoarm star terpolymers, PEO, and lithium salt (sodium salt) for AS-LMBs (AS-SMBs) (HEMI-ASPE-Li and HEMI-ASPE-Na, respectively), were prepared by the solution casting technique. To visually reveal the superiority of the HEMI-ASPEs, reference samples of the pure PEO-based ASPEs for AS-LMBs and AS-SMBs (PEO-ASPE-Li and PEO-ASPE-Na) were also prepared with the same salt/polymer mass ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that hydrogen bonds can improve the dispersion of the fillers. According to Shen's study, [ 43 ] cellulose@BN has a better shielding effect on polylactic acid due to its more uniform dispersion in the presence of hydrogen bonds. In Jiang's study, [ 44 ] the hydrogen bond was used to regulate the formation of the three‐dimensional boron nitride (3D BN) interconnected network to act as a high thermal conductive network in thermoplastic polyamide‐imide materials.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the BN particles were well compatible with PLLA-PEG-PLLA. In addition, there have no voids between dispersed BN particles and PLLA-PEG-PLLA matrix, which suggests that the interfacial between BN and PLLA-PEG-PLLA was stronger than the PLLA/BN composites [28]. The results indicated the PEG middle-blocks enhanced phase compatibility between BN and PLLA end-blocks.…”
Section: Phase Morphologymentioning
confidence: 90%
“…This indicates BN has poor shielding effect for improving the thermal stability on PLLA-PEG-PLLA. The movement of polymer chains of composites was restricted and gas barrier property was developed for obstructing the diffusion of decomposition products to improve thermal stability of polymer composites [28].…”
Section: 2 Thermal Decomposition Behaviorsmentioning
confidence: 99%